2017
DOI: 10.1186/s12879-017-2647-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic value of simultaneous amplification and testing for the diagnosis of sputum-scarce pulmonary tuberculosis

Abstract: BackgroundSince 20% of pulmonary tuberculosis (PTB) patients are asymptomatic, the early detection of PTB is a challenge particularly in sputum-scarce patients and diagnostic accuracy based solely on clinical characteristics and chest X-ray/CT scans are not always satisfactory. The AmpSure simultaneous amplification and testing method for the detection of Mycobacterium tuberculosis (SAT-TB assay) is an alternative approach to diagnose PTB. In the present study, we analyzed the usefulness of the SAT-TB assay fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Simultaneous Amplification and Testing (SAT) is one of the molecular biological detection methods used by the tuberculosis laboratory in China in recent years. It is mainly used to detect MTB in sputum to assist diagnosis [4][5][6][7]. However, SAT has rarely been used to test EPTB specimens and therefore, its sensitivity and specificity for EPTB diagnosis are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous Amplification and Testing (SAT) is one of the molecular biological detection methods used by the tuberculosis laboratory in China in recent years. It is mainly used to detect MTB in sputum to assist diagnosis [4][5][6][7]. However, SAT has rarely been used to test EPTB specimens and therefore, its sensitivity and specificity for EPTB diagnosis are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous Amplification and Testing (SAT) is one of the molecular biological detection methods used by the tuberculosis laboratory in China in recent years. It is mainly used to detect Mycobacterium tuberculosis (MTB) in sputum to assist diagnosis (Cui Z et al 2012;Zhang Q et al 2017;Yan L et al 2017;Chen Y et al 2018). However, SAT has rarely been used to test EPTB specimens and therefore, its sensitivity and specificity for EPTB diagnosis are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous amplification and testing method for TB is another fast molecular tool for MTB detection ( Fan et al, 2014 ; Yan et al, 2017 ). Previous studies showed that the specificity of SAT-TB is almost 100% in detecting PTB ( Yan et al, 2016a , b ), suggesting that SAT-TB has potential clinical value in the diagnosis of PTB as novel assay.…”
Section: Introductionmentioning
confidence: 99%